Economic performance of dairy cows fed diets with different levels of oregano - Oliveira, Julinessa Silva Oliveira de; Silva, Fabiano Ferreira da; Costa, Lucas Teixeira; Silva, Gonçalo Mesquita da; Meneses, Murilo de Almeida; Rodrigues, Eli Santana de Oliveira (Acta Scientiarum. Animal Sciences, 2014)
This study aimed to evaluate the economic viability of using different levels of oregano in diets for lactating cows fed sugar cane. We used 12 crossbred Holstein x Zebu cows assigned to three 4 x 4 Latin squares. The four treatments consisted of different levels of oregano: oregano free-control diet (0%) and diets added with 0.8, 1.6, and 2.4% oregano. Diets were formulated to meet the requirements for maintenance and milk production of 15 kg day-1. For economic analysis, we employed two economic indicators, net present value and internal rate of return. The total cost per animal and per liter of milk produced has increased with the inclusion of oregano. The inclusion of oregano was not effective for both productivity and profitability, with prices equal to R 0.87, 0.97, 1.09, 1.22, and R 0.78, 1.03, 1.28, and 1.52 of milk and concentrate, respectively for each level of inclusion. The internal rate of return was more advantageous when not adding oregano in the diet, indicating the viability of using oregano up to 0.8% inclusion to the diet of dairy cows under the conditions of this experiment. The net present value demonstrated that this investment is interesting for all discount rates used in the diet without the addition of oregano, pointing out that, in this treatment, the activity was feasible for any opportunity cost.